Phenomena identification and ranking table for passive residual heat removal system in IRWST. (August 2016) - Li, Xiangbin; Li, Nan; Wang, ZhongYi; Fu, Xiaoliang; Lu, Daogang; Yang, Yanhua
Highlights: Phenomenon identification for passive residual heat removal system was discussed. Importance levels of different parameters on heat transfer process were evaluated. The ranking table under various heat transfer stages was summarized. Abstract: The passive residual heat removal system (PRHR) plays an important role in AP1000 passive core cooling system during non-LOCA accidents. The temperature of the water in the in-containment refueling water storage tank (IRWST) will increase while the decay heat is removed through the C-tube heat exchanger under accident conditions, resulting in the change of heat transfer mechanism. Therefore, it is essential to study the relevant pool boiling phenomenon in IRWST by means of experiment. To ensure to capture the major ones from a large amount of influence factors associated with pool boiling in IRWST, the phenomena identification and ranking table (PIRT) was analyzed in this paper. The PRHR system was firstly divided into different modules and components based on the PIRT flow chart, and then the general factors associated with local heat transfer were discussed under different pool boiling stages. Finally, the importance levels of different parameters on heat transfer process were evaluated, which can provide some reference for future design of new PRHR system.